Malthus in the light of climate change - Lucas Bretschger (ETH Zurich, CER-ETH - Center of Economic Research, 2019)
To reconsider the Malthusian predictions of natural limits to economic development, the paper develops a multi-sector growth model with exhaustible resource extraction, investments in physical and knowledge capital, climate change, and endogenous fertility. Economic growth is driven by endogenous innovations which increase in the availability and productivity of research labour. Poor substitution of natural resources triggers sectoral change. Climate change is the result of polluting resource use which is, like consumption and investments, based on the intertemporal optimization of the households. Highlighting the importance of bounded resource supply and of rational extraction decisions I show that climate change is independent of population growth in steady state and there is no causal relationship between climate and population during transition to steady state. The consumption per capita growth rate rises in the innovation rate and the output elasticities of labour and capital in the different sectors. Unlike climate policy, population policy is not warranted; it may be counterproductive because labour is crucial for the research sector.
Keywords: Q43; O47; Q56; O41; 330; Population growth; climate change; endogenous innovation; sectoral change; fertility choice